2006
DOI: 10.1590/s0103-507x2006000300006
|View full text |Cite
|
Sign up to set email alerts
|

A doença oncológica não deve ser um fator limitante para admissão na UTI de pacientes submetidos a cirurgias de alto risco

Abstract: JUSTIFICATIVA E OBJETIVOS: A doença oncológica per se é uma condição que muitas vezes influencia no tratamento dispensado ao paciente. O objetivo do presente estudo foi comparar o desfecho hospitalar de pacientes oncológicos e não oncológicos submetidos à procedimentos cirúrgicos eletivos com alto risco de óbito. MÉTODO: Estudo de coorte prospectivo observacional, realizado em UTI de hospital terciário no período de 01 de abril a 31 de julho de 2005. Foram coletados dados demográficos, escore APACHE II, MODS,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…However, one of the major drawbacks of cost effectiveness analyses is that they do not normally take in to account factors such as patients’ age, mortality risk, resource utilization and survival benefit of admission (Ioannidis and Garber, 2011; Shmueli and Sprung, 2005; Iwashyna et al , 2015). Other studies also have shown that the defined admission indicators lack the precise predictability potential of ICU patient mortality and morbidity (Azoulay et al , 2001; Amendola et al , 2006; Higgins et al , 2003). In addition, these scores are not always valid and reliable methods of predicting patients’ health outcome.…”
Section: Study Literaturementioning
confidence: 99%
“…However, one of the major drawbacks of cost effectiveness analyses is that they do not normally take in to account factors such as patients’ age, mortality risk, resource utilization and survival benefit of admission (Ioannidis and Garber, 2011; Shmueli and Sprung, 2005; Iwashyna et al , 2015). Other studies also have shown that the defined admission indicators lack the precise predictability potential of ICU patient mortality and morbidity (Azoulay et al , 2001; Amendola et al , 2006; Higgins et al , 2003). In addition, these scores are not always valid and reliable methods of predicting patients’ health outcome.…”
Section: Study Literaturementioning
confidence: 99%
“…O estudo de Amendola et al [6] apontou que diante de procedimentos cirúrgicos de alto risco, pacientes oncológicos apresentaram mortalidade semelhante na UTI aos pacientes não oncológicos com gravidade de doença similar. Apesar disso, os autores [6] ainda destacam que existe um evidente preconceito à admissão de pacientes com câncer, apontando que pacientes com Doença Pulmonar Obstrutiva Crônica (DPOC) grave, insuficiência cardíaca classe IV ou cirrose possuem menor probabilidade de recusa de suporte terapêutico intensivo quando comparados a pacientes oncológicos.…”
Section: N T R O D U ç ã Ounclassified